(untitled) (Revista Contexto & Educação, 2026)
This study aimed to associate sociodemographic data and physical activity habits with the Executive Function (EF) of retired female teachers. This is a cross-sectional, quantitative, and inferential study. The sample was stratified into two groups: group 1, consisting of retired women without Pedagogy degree or higher education; and group 2, composed of retired female teachers. An evaluation form was used to record the participants’ personal, sociodemographic data, and health indicators. To assess physical activity habits, some questions related to the frequency, duration, intensity, and type of physical activity were asked. EF was assessed through performance on the Tower of Hanoi task. The data were analyzed using descriptive and inferential statistics. The EF performance of retired female teachers was significantly higher compared to that of retired women without training. It was identified that the length of study explained 18.31% of the variability in the volunteers’ EF. Retired participants without formal education and of older age showed poorer performance in Executive Function (EF). Finally, regular engagement in physical activity was associated with EF, with physically active participants being associated with a high prevalence of EF.